Estimating the national wage loss from cancer in Canada - Hopkins, R.B. (Multimed Inc., 2010)
OBJECTIVES: Using primary and secondary data sources, we set out to estimate the Canadian wage loss from cancer for patients, caregivers, and parents from a patient and a societal perspective. METHODS: First, a multiple-database literature search was conducted to find Canadian-specific direct surveys of wage loss from cancer. Second, estimates for wage loss were generated from the nationally representative Canadian Community Health Survey (cchs) Cycle 3.1. In addition, both estimates were standardized to derive a friction-period estimate and were extrapolated to produce national annual estimates. RESULTS: The literature search identified six direct surveys that included a total of 1632 patients with cancer. The cchs Cycle 3.1 included 2287 patients with cancer. Overall, based on the direct surveys, newly diagnosed cancer patients reduced their labour participation in the friction period by 36% ($4,518), and caregivers lost 23% of their workable hours ($2,887). The cchs estimated that annual household income was 26.5% lower ($4,978) for respondents with cancer as compared with the general population. For the year 2009, results from direct surveys indicated that new cancers in Canada generated a wage loss of $3.18 billion; the cchs Cycle 3.1 estimate was $2.95 billion. CONCLUSIONS: Wage loss from cancer is a significant economic burden on patients, their families, and society in Canada, with direct surveys and the cchs providing similar estimates.